Are skills rewarded in Sub-Saharan Africa? : determinants of wages and productivity in the manufacturing sector - Fox, Louise (Policy research working paper, 2008)
"Using recent matched employer-employee data from the manufacturing sector in 20 Sub-Saharan African countries, the authors analyze how the supply of skills and legal origin of the country affect the wage setting process. The wage analysis yields three main findings. First, increasing returns to education, especially for older workers, suggest that the expansion of education in Africa has reduced returns to education for entrants in the labor market. Second, age effects matter not just for returns to education, but also for the wage setting process more generally. In particular, in civil-law countries, returns to seniority are rewarded only after a certain age. Third, workers exercise some power in the wage setting process but their influence varies by linguistic group. In common-law countries, union presence benefits all workers equally, not just members, whereas in civil-law countries, only older members enjoy higher wages. The authors also contrast wage premia with relative marginal productivities for different age, occupation, and education categories. The findings show that in general, older, highly educated, and highly ranked workers receive wage premia that do not reflect a higher relative marginal productivity. "--World Bank web site